Bullying, ciberbullying e problemas de comportamento : o género e a idade importam? - Carvalho, Marina (2019)
The main goal of this study was to analyze the effect of gender and age on the involvement in bullying, cyberbullying and violence situations. For this purpose, a random sample composed of 8215 students who participated in the study, 52.7% female, mean age of 14.36 years (SD = 2.28), who attended the 6th, 8th, 10th and 12th grades were studied. In the scope of the present study, the indicators related to the involvement in bullying and cyberbullying situations and in behavioral problems, as well as callous-unemotional traits, were analyzed. The association between gender and grade with the variables under study was analyzed through Chi-Square tests. Gender and grade differences for behavioral problems and callous-unemotional traits were studied through Student’s t-tests and analysis of variance. Females reported being more involved in bullying and cyberbullying as victims and males as aggressors and/or provocative victims; boys reported more behavioral problems and more callous-unemotional traits. Finally, the involvement in situations of violence has also shown, according to the literature, a decrease with age. These results demonstrated the importance of the development of prevention programs paying attention to the role of gender and age, and especially of characteristics that, although still less studied, such as callous-unemotional traits, can play a moderating role.